Development of ‘Reaksi’ Digital Media Supplement for Enhancing Moral Character Understanding of Phase A - Silvy Fuji Risnawati; Muhamad Riva Fauzan; Septika Hani Dafana Azzahra; Ani Nur Aeni (Dirasah: Jurnal Pendidikan Islam, 2026)
Findings from the implementation phase indicate that the average pre-test score was 100.00 (SD = 0.00) and the average post-test score was 93.13 (SD = 8.96). The decrease in the average score was accompanied by an increase in the standard deviation, indicating a more comprehensive assessment of understanding. Approximately 93.75% of students scored above 80, indicating a high level of knowledge. The study demonstrates that the digital media “REAKSI” is suitable and beneficial as an additional educational resource for enhancing student morale. This research emphasizes the importance of incorporating value-based digital media into elementary education to support character development in the digital age. Validation results indicate that the “REAKSI” media is categorized as highly suitable, with an average score of 4.00 for each evaluation criterion on a 1–4 scale. Experimental results show a ceiling effect, with an average pre-test score of 100.00 (SD = 0.00), indicating that all students had a strong initial understanding of the moral material being assessed. The average post-test score was 93.13 after using the media, with a standard deviation of 8.96. The Wilcoxon signed-rank test showed no significant difference between the pre-test and post-test (Z = -1.732, p = 0.083 > 0.05), indicating that the decrease in scores was not statistically significant. The learning achievement rate (KKM ≥80) reached 93.75%, and the increase in standard deviation indicates that the post-test assessed higher cognitive levels compared to the pre-test. The “REAKSI” digital media is considered suitable and beneficial as a supplementary learning tool to enhance students’ moral understanding in Stage A of elementary school